Silica Activity Measurements in the Y2O3–SiO2 System and Applications to Modeling of Coating Volatility. Issue 6 (12th May 2014) - Jacobson, Nathan S.; Butt, D.
<x xml:space="preserve">Abstract</x> Rare‐earth silicate compounds, such as those in the Y2O3–SiO2 system, are promising candidates for coatings of SiC‐based ceramics and ceramic matrix composites in combustion environments. The predicted lower activity of silica in these silicates will lead to less reactivity with the water vapor combustion products. A procedure for measuring silica activities in this system is discussed. Knudsen effusion mass spectrometry is used and the measured vapor pressure of SiO(g) is correlated to activity. Due to the low vapor pressure of SiO(g) in the temperature range of interest, a reducing agent is utilized to boost this vapor pressure without altering the solid‐state composition. In addition, corrections are made for nonequilibrium vaporization. The measured silica activities are: Y2O3 + Y2O3·SiO2 two phase field: log[a(SiO2)] = −5200.26(1/T) + 0.0567 (1532 < T(K) < 1670) Y2O3·SiO2 + Y2O3·2SiO2 two phase field: log[a(SiO2)] = 4.2252(1/T)−0.5531 (1628 < T(K) < 1747) It is shown how these results can be used to predict reduced volatilization rates of the coatings.